Pengaruh Jumlah Penduduk, Proporsi Perempuan dan Pertumbuhan Ekonomi Terhadap Pengangguran di Provinsi Sumatera Utara - Daulay, Muhammad Apis; Abdul Haris (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
The study aims to analyze the impact of the population, the proportion of women, and economic growth on the unemployment rates in the province of North Sumatra during 2018–2021. The research data used secondary data from the Central Statistical Authority (BPS) of North Sumatra. The research method used the best model selection estimate test and processed the fixed-effect model (FEM), and the analysis technique used the regression analysis of panel data. The results show that the variable of the proportion of women has a negative influence on the number of dismissals. The results of this study can provide a basis for supporting policies that encourage women's economic participation. This may involve efforts to improve access to education and training for women and create better employment opportunities, while the population and economic growth have no influence on the unemployment rate in the province of North Sumatra in 2018–2021. The research can make a positive contribution to addressing the unemployment problem in the Province of North Sumatra and fostering sustainable development.